The Rhythmic Structure of Music - Cooper, Grosvenor; Meyer, Leonard B. (Chicago, IL University of Chicago Press, 1960)
In this influential book on the subject of rhythm, the authors develop a theoretical framework based essentially on a Gestalt approach, viewing rhythmic experience in terms of pattern perception or groupings. Musical examples of increasing complexity are used to provide training in the analysis, performance, and writing of rhythm, with exercises for the student's own work.
Keywords: Rhythm